Prenatal diagnostic testing and atypical chromosome abnormalities following combined first‐trimester screening: implications for contingent models of non‐invasive prenatal testing. (10th April 2018) - Lindquist, A.; Poulton, A.; Halliday, J.; Hui, L.
Abstract : Objectives: To investigate by means of a population‐based analysis of a cohort of women who underwent combined first‐trimester screening (CFTS), changes in uptake of invasive prenatal diagnosis according to risk of trisomy 21 (T21) on CFTS, and prevalence and methods for ascertainment of atypical chromosome abnormalities. Methods: This was a retrospective cohort study using state‐wide prenatal datasets from Victoria, Australia. A three‐step approach was taken to analyze the data: (1) linkage of records between serum screening and diagnostic results; (2) comparison of rates of diagnostic testing according to CFTS T21 risk result category in a 2014–2015 cohort with those of a historical 2002–2004 cohort; (3) detailed analysis of atypical abnormalities in the 2014–2015 group according to CFTS T21 risk result, individual serum analyte level and other indications for invasive diagnostic testing. Results: In 2014–2015, there were 100 418 CFTS results issued for 146 776 births (68.4%). The overall prevalence of atypical chromosome abnormalities in the entire CFTS cohort was 0.10% and was highest in those with CFTS T21 risk > 1 in 10 (4.6%), or serum analyte levels < 0.2 multiples of the median (MoM) (6.9% for pregnancy‐associated plasma protein‐A (PAPP‐A) and 5.2% for beta‐human chorionic gonadotropin ( β ‐hCG)). Almost half (49.2%) of women with PAPP‐A < 0.2 MoM had a risk for T21 on CFTS of less than 1 in 100. The majority (55%) of atypical abnormalities occurred in women with CFTS T21 risk below 1 in 300, and were most commonly detected on ultrasound examination (47.1%). Conclusion: Concerns regarding missed diagnoses of atypical chromosome abnormalities when non‐invasive prenatal testing is offered after a result of high risk on CFTS can be mitigated if invasive diagnostic testing is offered to those women with CFTS T21 risk of > 1 in 100, serum PAPP‐A or β ‐hCG < 0.2 MoM, or ultrasound‐detected abnormality. This has implications for contingent models of screening. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.